The wizard and the prophet : two remarkable scientists and their dueling visions of tomorrow's world - Mann, Charles C. (Alfred A. Knopf, 2018)
Two influential scientists, William Vogt (1902-1968), and Norman Borlaug (1914-2009), and their approaches to environmental problems.